Teachersâ€™ Perceived Challenges of Using ICT in Teaching Secondary School Social Science Subjects in Ilorin, Nigeria - Olokooba, Issa Nasiru; Okunloye, Rotimi William; Abdulsalam, Alliyu Ayodele; Balogun, Idayat Nike (NIU Journal of Humanities, 2018)
Information and Communication Technology (ICT) has contributed immensely to human learning and teaching by simplifying difficult concept and enhancing accessibility to contemporary data and developments in human societies in all fields and forms of knowledge, especially social sciences which study human interaction in time and space. However, developing countries such as Nigeria have been experiencing challenges in other sectors that are ICT driven. Therefore, it is necessary to ascertain the nature of this challenges in the school system where it has become a set of tool used by teachers for enhancing learnability of school curriculum and improving academic achievement. Therefore, this study examined the teachersâ€™ perceived challenges of using ICT in teaching secondary school Social Studies Subjects in Ilorin, Nigeria. Specifically, the study identified the teachersâ€™ perceived challenges of ICT use in social science subjects in classroom situations and influence of gender and school proprietorship on the challenges. Descriptive survey research design was employed. Population for this study comprised all social science teachers in Ilorin. The sample for this study comprised 300 respondents through a stratified random sampling technique. A questionnaire titled â€œChallenges of using ICT in Secondary Schools (CICTSS)â€ was used. Its reliability was obtained using the test-retest method index of 0.78. Three research questions were raised, a research question was answered using mean and standard deviation while two corresponding hypotheses were tested using t-test statistic. Findings of the study showed that many challenges such as unavailability of computer laboratory, lack of instructional software, the inefficiency of teachersâ€™ technical knowledge, irregular power supply and poor maintenance of computer systems are the constraints in use of ICT facilities by social science teachers. The study also revealed that there is no statistically significant difference between male and female (t=0.29, p>0.05), and private and public social science teachers (t=0.26, p>0.05) on the challenges associated with the use of ICT facilities in schools. Based on these findings, it was recommended among other that regular workshops, seminars, and in-service training should be organised to improve teachersâ€™ efficiency on the usage of ICT.